Cultivo do pimentão sob água tratada por energização e doses de biofertilizante - Borges, Francisca Robevania Medeiros (2012)
Water is an essential factor in agriculture, which justifies the technological research seeking ways to rationalize its use. This rationalization is even less dispensable when considering the search for planetary sustainability, demanding food grown without environmental degradation. In this context, this study was aimed at evaluating the effect of energized water and different doses of biofertilizer on growth, yield and post-harvest of the Línea R-F1 hybrid bell pepper (Capsicum annuum L.). The experiment was conducted in pots with 40 L capacity at the site of the Meteorological Station of the Departamento de Engenharia Agrícola, Universidade Federal do Ceará in Fortaleza (CE). The experimental design was that of randomized blocks in split plots with four replicates, with the subplots corresponding to the irrigation with water energized and not energized (treatments) and the plots corresponding to five doses of cattle biofertilizer (0, 250, 500, 750 and 1000 mL plant-1 week-1). Growth analysis of plant height, stem diameter and number of leaves were collected at 27, 42, 55, 69, 83, 97, 112 and 173 days after transplant (DAT). The harvest was carried out weekly, the first being made at 85 DAT. The characteristics evaluated were: plant height (AP), stem diameter (DC), number of leaves (NF), leaf dry matter (MSF), stem dry matter (MSC), average fruit weight (PMF) number of fruits per plant (NF), fruit yield per plant (PROD), productivity (PROD ha-1), fruit length (CF), axial fruit diameter (DF), flesh thickness (EP) and soluble solids (SS). The results showed that irrigation with energized water did not significantly influence either the growth and production variables nor the post-harvest characteristics of the hybrid yellow bell peppers. The application of biofertilizer statistically influenced the analyzed growth variables, obtaining a linear increase with increasing biofertilizer doses, except with AP and MSF. There was significant interaction between energizing water treatment and DAT for AP, and between biofertilizer doses and DAT for the variables DC and NF. Arranging the biofertilizer doses in an increasing order, it corresponded to a linearly corresponding increase in the variables of productivity and post-harvest, with the highest values corresponding to the highest applied biofertilizer dose (1000 mL plant-1 week-1). The maximum bell pepper yield of 19,045 kg ha-1 obtained from the dose of 1000 mL plant-1 week-1, was in accordance with an organic production, and was 55.7% higher than the 8444.2 kg ha-1 yield achieved with the control.